HOW SOCIAL MEDIA SHAPES INTERCULTURAL LANGUAGE EXCHANGE: HOW SOCIAL MEDIA SHAPES INTERCULTURAL LANGUAGE EXCHANGE - Турсынмуратова, Замира (Журнал иностранных языков и лингвистики, 2025)
munication but also for language learning through intercultural exchange. Intercultural language exchange, where individuals from diffrent cultural and linguistic backgrounds interact to learn from one another, has seen a significant transformation due to the rise of social media platforms such as Facebook, Instagram, TikTok, and language learning applications like Tandem and HelloTalk